Two patients treated with pegylated interferon/ribavirin/telaprevir triple therapy for recurrent hepatitis C after living donor liver transplantation. Issue 12 (17th February 2014) - Kawaoka, Tomokazu; Takahashi, Shoichi; Tatsukawa, Yumiko; Hiramatsu, Akira; Hiraga, Nobuhiko; Miki, Daiki; Tsuge, Masataka; Imamura, Michio; Kawakami, Yoshiiku; Aikata, Hiroshi; Ochi, Hidenori; Ishiyama, Kouhei; et al.
Abstract : It is difficult to use protease inhibitors in patients with recurrent hepatitis C virus (HCV) infection after liver transplantation (LT) due to interaction with immunosuppressive drugs. We report our experience with two patients treated with telaprevir (TVR) combined with pegylated interferon/ribavirin (PEG IFN/RBV) for recurrent HCV genotype 1 infection after LT. The first was a 63‐year‐old man with HCV‐related liver cirrhosis, who failed to respond to IFN‐β plus RBV after LT. Treatment was switched to PEG IFN‐α‐2b plus RBV and TVR was started. The donor had TT genotype of interleukin (IL)‐28 single nucleotide polymorphisms (SNP) (rs8099917). The recipient had TT genotype of IL‐28 SNP (rs8099917). Completion of 12‐week triple therapy was followed by PEG IFN‐α‐2b plus RBV for 36 weeks. Finally, he had sustained viral response. The second was a 70‐year‐old woman with HCV‐related liver cirrhosis and hepatocellular carcinoma. She failed to respond to PEG IFN‐α‐2b plus RBV after LT, and was subsequently switched to PEG IFN‐α‐2b/RBV/TVR. Genotype analysis showed TG genotype of IL‐28 SNP for the donor, and TT genotype of IL‐28 SNP for the recipient. Serum HCV RNA titer decreased below the detection limit at 5 weeks. However, triple therapy was withdrawn at 11 weeks due to general fatigue, which resulted in HCV RNA rebound 4 weeks later. Both patients were treated with cyclosporin, starting with a small dose to avoid interactions with TVR. TVR is a potentially suitable agent for LT recipients who do not respond to PEG IFN‐α‐2b plus RBV after LT.